Transporteurs et propriétaires terriens en Gaule romaine : un bilan - Jean-Claude Béal (Revue Archéologique du Centre de la France, 2008)
Nowadays we are beginning to have a better understanding of artisan activity in villas. However the owners of rural properties were equally able to have a transport activity, which can, in some cases, be highlighted. It developed either linked to local production, of wine or stone for example, or thanks to a convergence of road and river networks; it contributed to the revenue of the villa.